UV-Vis Spectroscopic Study on a New Synthesized 4-Hydroxy-N-[(E)-(2-hydroxyphenyl)methylidene]benzohydrazide as Calorimetric Reagent For Mg2+ Ions - Tameem, Abdassalam A. A.; Mohamed, Abdussalam S. (Journal of Pure & Applied Sciences, 2022)
This study is concerned about the study of the chromogenic properties of hydrazone compound, i.e. 4-hydroxy-N-[(E)-(2-hydroxyphenyl)-methylidene]benzo-hydrazide towards magnesium ion recognition. The hydrazone compound was synthesized and characterized by FT-IR and NMR spectroscopy. The complexation ability of the studied ligand towards Mg2+ was investigated using UV-Vis spectroscopy. Experimental parameters that affect the ligand-metal ion complexation such as effect of solvent, standing time, metal concentration and ligand concentration were investigated. Results show that HNHMB is preferentially to bind with Mg2+ in ethanol. The addition of Mg2+ to the ligand in ethanol gives rise to a large hyerchromic shift resulting in a colour darkness. From the linear regression analysis, Beer’s law was obeyed in at least 0.1–1.4× 10-4 M. The complex showed maximum absorptions (λmax) at 396 nm.